A typology of the sources of mental health precarity among migrant workers in India during the COVID-19 lockdown - Mookerjee, Devalina; Roy, Shubhabrata (Frontiers in Communication, 2023)
When urban workplaces shut down for the COVID19 pandemic lockdown in India, a very large number of migrant workers were forced to reverse-migrate to their rural homes. This paper looks at the mental health implications of the period migrants spent without work, back at the places from which they had out-migrated in search of a better life. Based on qualitative interviews conducted with reverse migrants during the pandemic lockdown, this paper has a two-fold aim. The first aim is to reach the experiences and voiced concerns of marginalized and vulnerable migrants to those who may be in a position to ameliorate their distress. Since policy-makers tend to lack time, findings from the qualitative data have been summarized in the form of an exploratory typology, open to expansion by further research. The typology sees superordinate themes in money, health, information, the individual in society, and the future. Second, the paper follows the issues in the typology to suggest that acknowledgement of the significant role of migrant workers in India’s economy, via sensitive enumeration, would be a first, and essential step to address the concerns raised by migrant workers themselves. This baseline information could then be used to build subsequent dependent steps addressing the myriad causes of mental health distress among migrant workers in India.